2002
DOI: 10.1094/pdis.2002.86.9.1014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic and Inorganic Salts on the Development of Helminthosporium solani, the Causal Agent of Potato Silver Scurf

Abstract: Potato silver scurf, caused by Helminthosporium solani, is an important postharvest disease of economic significance. Control of H. solani has been accomplished primarily by postharvest applications of thiabendazole. However, many strains of H. solani have become resistant to thiabendazole, resulting in failure of disease control. Consequently, alternative control strategies are needed. This study showed that several salts significantly reduced silver scurf development on potato tuber at a concentration of 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 24 publications
5
52
0
5
Order By: Relevance
“…On the other hand, one pathogen could be inhibited by various salts. These results are consistent with many other reports [17,27,[70][71][72]. In fact, these salts possess wide-spectrum antimicrobial properties and have been demonstrated to inhibit the growth of several fungal pathogens infecting stored fruits, vegetables, and ornamental species [17,[19][20][21][22].…”
Section: Vd Fol Forlsupporting
confidence: 93%
“…On the other hand, one pathogen could be inhibited by various salts. These results are consistent with many other reports [17,27,[70][71][72]. In fact, these salts possess wide-spectrum antimicrobial properties and have been demonstrated to inhibit the growth of several fungal pathogens infecting stored fruits, vegetables, and ornamental species [17,[19][20][21][22].…”
Section: Vd Fol Forlsupporting
confidence: 93%
“…Recent studies suggest that salt application reduces postharvest potato diseases. Olivier et al (1998) and Hervieux et al (2002) showed that application of potassium sorbate, calcium propionate, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, and ammonium bicarbonate at 0.2 M reduced silver scurf lesion development and Helminthosporium solani sporulation on inoculated and naturally infected potato tubers. These reports confirm the obtained results in the present study showing that sodium bicarbonate was found to be strongly inhibiting to mycelial growth of A. solani at concentrations of 20 and 30 mg/ml either under in vitro or in vivo trails.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Helminthosporium velutinum and H. aquaticum in Helminthosporium sensu stricto, we included the isolates of H. solani with the sequence data available in GenBank. Helminthosporium solani is an important plant pathogen that causes silver scurf disease on potato, resulting in a cosmetic surface blemish to the tubers, and weight loss in storage (Firman & Allen 1995, Olivier et al 1998, Hervieux et al 2002. Helminthosporium aquaticum is close to H. velutinum in morphology and DNA sequence data (Fig.…”
Section: Discussionmentioning
confidence: 98%